The Oldest Fossils From China Provide the Most Direct Evidence for the Ancestral State of Fossula Spongiosa and Stridulitrum of Reduviidae - Zhang, Peipei; Liu, Yingqi; Ren, Dong; Yao, Yunzhi (Frontiers in Ecology and Evolution, 2022)
This study describes two Reduviinae fossil species, Simplicivenius tuberculosus gen. et sp. nov. and Simplicivenius rectidorsius gen. et sp. nov. from the Yixian Formation in northeastern China, and establishes a new fossil genus based on the morphological characters of two fossils. The diagnosis of the genus includes the width of the scutellum about 2/3 of the width of the pronotum and the absence of longitudinal veins around the exterior cell of the membrane. This is the oldest fossil record of Reduviinae and indeed Reduviidae at present, dating back to the Early Cretaceous. This implies that Reduviinae existed before the Late Cretaceous biological mass extinction, hinting that Reduviinae may be a basal taxon within the Higher Reduviidae. Moreover, the fossils prove the correctness of the previous speculations on the ancestral state of the stridulitrum and fossula spongiosa of the assassin bugs. The fossula spongiosa on mid leg and fore leg are subequal in size and both occupy 1/3 of the tibia is considered the primitive type of fossula spongiosa.